Dorsal Pancreatectomy: An Alternative to the Total Pancreatectomy. Report of Two Cases and Review of the Literature - Iacono, Calogero; Ruzzenente, Andrea; Valdegamberi, Alessandro; Bertuzzo, Francesca; Conci, Simone; Bagante, Fabio; Xillo, Laura; Guglielmi, Alfredo (JOP. Journal of the Pancreas, 2012)
Context For the last three decades several advances in technique in pancreatic surgery have been performed in order to preserve pancreatic parenchyma. Dorsal pancreatectomy is a parenchyma-sparing segmental pancreatic resection, carried out to avoid exocrine or endocrine failure or biliary and gastrointestinal reconstruction. Case reports In this paper two cases of dorsal pancreatectomy were reported. In both cases, the excision of the entire dorsal pancreas was performed with preservation of the biliary duct and the spleen, the gastroduodenal artery was preserved to avoid ischemia of the bile duct and duodenum. The first patient was a 71-year-old female affected by IPMN of the tail of pancreas with a small liver metastasis intra-operatively detected and removed. The post-operative course was uneventful. The patient was discharged 13 days after surgery and then submitted to systemic and intra-arterial regional chemotherapy (FLEC regimen). This patient died 30 months after surgery for liver and peritoneal recurrences, without signs of endocrine insufficiency but with necessity to intake a low-dose pancreatic enzymes. The second patient was a 35-year-old female affected by solid pseudopapillary tumor involving the head and the neck of the pancreas with atrophy of the distal part of pancreatic parenchyma. The post-operative course was uneventful and the patient was released on the 11th post-operative day. Seventy-five months after surgery the patient is still alive, in absence of diabetes or exocrine impairment.